The Profitability Analysis on Company Value Using Islamic Social Reporting as a Moderating Variable - Dinda Fali Rifan; Maria Hodijah (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2023)
The value of company is generally measured through the share price. The high company value is generally indicated by increasing the share price of a company in the market. For companies listed in the Jakarta Islamic Index (JII), the high share prices are not accompanied by the high profitability values, either decreasing or increasing. The profitability indicator is measured through Return on Assets (ROA). Therefore, ISR was added as a moderating variable in this research. This research aims to determine the effect of the profitability variable on the company value variable with Islamic Social Reporting (ISR) as a moderating variable in companies listed in the Jakarta Islamic Index (JII) for 2019-2021. This study uses a quantitative approach. Sampling was carried out using a purposive sampling technique, as well as data processing using SmartPLS version 4. This research concludes that the profitability as proxied through ROA has no effect on the company value. Apart from that, ISR disclosure as a moderating variable cannot influence the relationship between profitability and company value.